Pengaturan Parate Eksekusi Objek Jaminan Fidusia Pasca Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 - Sinta Bella, Devi; Yahya, Taufik; Hasan, Umar (Recital Review, 2025)
This article aims to analyze the provisions on parate execution of fiduciary guarantees and their legal consequences following Constitutional Court Decision Number 18/PUU-XVII/2019. Prior to this decision, creditors had the authority to execute fiduciary guarantees directly without going through the courts when the debtor defaulted. However, the Constitutional Court emphasized that parate execution can no longer be carried out unilaterally, but must be based on an agreement regarding the default or through a court order. The research method used is normative juridical with a statutory, conceptual, and case approach, with legal materials in the form of regulations, literature, and court decisions analyzed qualitatively. The results show that this decision provides greater protection for debtors because execution can no longer be carried out without judicial oversight. On the other hand, creditors lose the certainty of automatic execution, which implies increased financing risks, additional costs, and potential delays in the execution process. This condition affects the policies of financial institutions in disbursing fiduciary-based credit. Thus, this decision emphasizes the need for a balance between protecting debtors' rights and legal certainty for creditors, while also encouraging the existence of derivative regulations and technical guidelines so that the implementation of fiduciary execution following the Constitutional Court's decision can be effective, fair, and provide legal certainty.